ND630 controls ACACA and lipid reprogramming in prostate cancer by regulating the expression of circKIF18B_003 - Wu, Yu-Peng; Zheng, Wen-Cai; Huang, Qi; Huang, Xu-Yun; Lin, Fei; Ke, Zhi-Bin; You, Qi; Zheng, Qing-Shui; Wei, Yong; Xue, Xue-Yi; Xu, Ning (Journal of translational medicine, 2023)
ND630 is believed to be a new therapy pharmacologic molecule in targeting the expression of ACACA and regulating the lipid metabolism. However, the function of ND630 in prostate cancer remains unknown. KIF18B, as an oncogene, plays a vital role in prostate cancer progression. circKIF18B_003 was derived from oncogene KIF18B and was markedly overexpressed in prostate cancer tissues. We speculated that oncoprotein KIF18B-derived circRNA circKIF18B_003 might have roles in prostate cancer promotion. The aim of this study was to validate whether ND630 could control ACACA and lipid reprogramming in prostate cancer by regulating the expression of circKIF18B_003. RT-qPCR was used to analyze the expression of circKIF18B_003 in prostate cancer cell lines and prostate cancer samples. circKIF18B_003 expression was modulated in prostate cancer cells using circKIF18B_003 interference or overexpression plasmid. We examined the function and effects of circKIF18B_003 in prostate cancer cells using CCK-8, colony formation, wound healing, and Transwell invasion assays and xenograft models. Fluorescence in situ hybridization (FISH) was performed to evaluate the localization of circKIF18B_003. RNA immunoprecipitation (RIP), RNA pull down, and luciferase reporter assay were performed to explore the potential mechanism of circKIF18B_003. The function of ND630 was determined in this study. circKIF18B_003 was overexpressed in prostate cancer tissues, and overexpression of circKIF18B_003 was associated with poor survival outcome of prostate cancer patients. The proliferation, migration, and invasion of prostate cancer cells were enhanced after up-regulation of circKIF18B_003. circKIF18B_003 is mainly located in the cytoplasm of prostate cancer cells, and the RIP and RNA pull down assays confirmed that circKIF18B_003 could act as a sponge for miR-370-3p. Further study demonstrated that up-regulation of circKIF18B_003 increased the expression of ACACA by sponging miR-370-3p. The malignant ability of prostate cancer cells enhanced by overexpression of circKIF18B_003 was reversed by the down-regulation of ACACA. We found that overexpression of circKIF18B_003 was associated with lipid metabolism, and a combination of ND-630 and docetaxel markedly attenuated tumor growth. ND630 could control ACACA and lipid reprogramming in prostate cancer by regulating the expression of circKIF18B_003. ND630 and circKIF18B_003 may represent a novel target for prostate cancer.